Appraising the criteria for contractors’ prequalification on selected public tertiary educational building projects in Southwestern Nigeria - Adedokun, Olufisayo Adewumi (Penerbit Universiti Kebangsaan Malaysia, 2020)
The success of any construction project is dependent on construction contractor to a great extent. Therefore, it is of paramount essence to select a qualified contractor in the execution of construction projects. This study aims at identifying the important criteria for selection of contractor which can be leveraged upon by the client in order to achieve successful building projects. With questionnaire survey adopted, the study recorded high response rate of 65%, out of 120 questionnaires administered on the respondents, above the usual trend of 20-30%. The questionnaire used and data collected were valid and reliable respectively. The Cronbach alpha values of reliability analysis range between 0.732 and 0.910. It was found that the major criteria for tertiary educational building (TEB) projects procured via open tendering route are bid amount and financial soundness while technical ability and management capability are for selective tendering arrangements. Regardless of the routes employed to actualize TEB projects, capital bid, financial status, experience, experience of technical personnel and client-contractor relationship are the most important sub-criteria for contractors’ prequalification. The study recommends that not only construction client should give adequate cognizance to the aforementioned criteria but also the contractor during pursuit of better evaluation of bids technically and financially.